2012
DOI: 10.1590/s1806-83242012005000024
|View full text |Cite
|
Sign up to set email alerts
|

Oral leukoplakia manifests differently in smokers and non-smokers

Abstract: Oral leukoplakias (OL) are potentially malignant lesions that are typically white in color. Smoking is considered a risk factor for developing OL, and dysplastic lesions are more prone to malignant transformation. The aim of this study was to describe the clinical features observed in dysplastic and non-dysplastic OL in both smokers and nonsmokers. A total of 315 cases of OL were retrieved and separated into either dysplastic or non-dysplastic lesions, and these cases were further categorized as originating in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
3
9
0
Order By: Relevance
“…Male patients were predominant in both conventional type and smokeless type which was in accordance with studies conducted by Saraswathi et al ( 11 ), and Ray et al ( 12 ), whereas Female predominance was seen in studies conducted by Lima et al ( 13 ).…”
Section: Discussionsupporting
confidence: 89%
“…Male patients were predominant in both conventional type and smokeless type which was in accordance with studies conducted by Saraswathi et al ( 11 ), and Ray et al ( 12 ), whereas Female predominance was seen in studies conducted by Lima et al ( 13 ).…”
Section: Discussionsupporting
confidence: 89%
“…In our study, leukoplakia was observed in 2.7% of patients 21. In another study also smoking had a huge correlation with the frequency of leukoplakia in the oral cavity 22. Smoking tobacco is the most responsible factor for the development of intraoral white lesions.…”
Section: Discussionsupporting
confidence: 56%
“…There are two reasons for this controversy: first, the diagnosis of leukoplakia is made by exclusion; and second, leukoplakia is a clinical entity that can present with different histological, molecular and genetic patterns. 20,21 The use of EC in leukoplakia has been questioned because the lesion is keratotic and non-ulcerated; these characteristics are associated with a contraindication of the technique. However, EC can be used for selecting the best area for biopsy in large leukoplakia lesions.…”
Section: Discussionmentioning
confidence: 99%